Open-Ended Problems for Junior High School Students’ Mathematical Reasoning - Yatha Yuni; Andri Suryana (IndoMath: Indonesia Mathematics Education, 2020)
The abilities that must be mastered by high school students according to the demands of the 2013 curriculum include reasoning. Students who have good reasoning abilities make it easier to understand mathematics. But in reality there are still many students who have low mathematical reasoning ability, seen when they have difficulty solving math problems. This research objective is to prove the habit of solving open-ended problems that can improve the mathematical reasoning ability of junior high school students based on the level of initial mathematical ability: high, medium, and low. The study used an experimental method with a "One-Group pre-test post-test design". Randomly, selected 77 grade VII students of SMP Negeri in Bekasi as a sample. The prerequisite test shows that each level of data comes from groups that are normally distributed and homogeneous. The results showed normal gain, both overall and level showed improvement. Based on the t test obtained p value of 0.000 < 0.005, meaning this study can prove student habits in solving open-ended problems when learning mathematics on triangles and quadrilateral, can improve students' mathematical reasoning abilities.